Isolated fallopian tube torsion associated with hydrosalpinx: case report and review of the literature - Trainavičius, Rokas; Mongirdas, Matas; Povilavičius, Jonas; Trainavičius, Kęstutis (Lietuvos chirurgija, 2018)
[full article and abstract in Lithuanian; abstract in English]Background. Isolated fallopian tube torsion due to hydrosalpinx is a rare cause of obdominal pain in adolecent patients. The incidence in reproductive age woman is 1:1 500 000. Only few cases have been reported of isolated fallopian tube torsion caused by hydrosalpinx in pediatric patients. The clinical manifestation is non-specific and usually diagnosis is set during diagnostic laparoscopy.Case report. We present the case of 11 year old virgin girl, presented with acute lower right-sided abdominal pain. No specific symptoms were identified. Ultrasound showed an elongated cystic mass, measuring 80 mm in length and 15 mm width in the pelvic cavity. Hydrosalpinx of the right fallopian tube was suspected. The patient was scheduled for an laparoscopic operation, during which an enlarged and twisted fallopian tube was found. Detorsion ant puncture was performed.Conclusion. Isolated fallopian tube torsion is very rare in adolescent patients and it can be often misdiagnosed. Although uncommon, isolated fallopian tube torsion should be included in every case of abdominal pain differential diagnosis.
Keywords: hydrosalpinx, isolated fallopian tube torsion, children, laparoscopy